2014
DOI: 10.1148/radiol.14140047
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MR Imaging of Brain Iron in Attention Deficit Hyperactivity Disorder: A Noninvasive Biomarker That Responds to Psychostimulant Treatment?

Abstract: ).q RSNA, 2014 Purpose:To comprehensively assess brain iron levels in typically developing control subjects and patients with attention deficit hyperactivity disorder (ADHD) when psychostimulant medication history is accounted for. Materials and Methods:This prospective study was approved by the institutional review board, and informed consent was obtained. Brain iron was indexed noninvasively by using magnetic resonance (MR) imaging relaxation rates (R2, R2*, R29) and magnetic field correlation (MFC) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 37 publications
5
76
2
Order By: Relevance
“…The number of participants varied across studies, and ranged from 27 to 1260. Four studies were conducted in Europe [8, 13, 14, 18], one in the USA [11], one in Egypt [19], one in Brazil [20], and four in Asia [10, 2123]. With the exception of three studies [8, 22, 23], all included studies reported medication use in the patients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of participants varied across studies, and ranged from 27 to 1260. Four studies were conducted in Europe [8, 13, 14, 18], one in the USA [11], one in Egypt [19], one in Brazil [20], and four in Asia [10, 2123]. With the exception of three studies [8, 22, 23], all included studies reported medication use in the patients.…”
Section: Resultsmentioning
confidence: 99%
“…The Galbraith radial plot graph (Fig 4) showed four studies [8, 10, 11, 18] that might contribute to the high heterogeneity across studies. Further sensitivity analysis indicated that the overall pooled results did not vary substantially after omitting each of the four studies one at a time (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations